2009
DOI: 10.1097/jcp.0b013e31819b95fc
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal Markers of Metabolic Dysregulation in Patients With Severe Mental Disorders After Olanzapine Treatment Under Real-Life Conditions

Abstract: Alterations in several interrelated metabolic hormonal markers were associated with olanzapine treatment, independent of body mass, particularly in female subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 50 publications
1
21
1
Order By: Relevance
“…57 Moreover, we included only chronic male patients in this study. Since previous studies 35,58,59 have indicated gender differences in antipsychotic-induced dysmetabolism, our findings may not be readily applied on a female population. Except for the absence of gender effects, our naturalistic study design and consecutive enrollment of subjects increase the external validity of the present study.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…57 Moreover, we included only chronic male patients in this study. Since previous studies 35,58,59 have indicated gender differences in antipsychotic-induced dysmetabolism, our findings may not be readily applied on a female population. Except for the absence of gender effects, our naturalistic study design and consecutive enrollment of subjects increase the external validity of the present study.…”
Section: Discussionmentioning
confidence: 64%
“…35, 56 Yet, in a recent study, 41 fasting leptin levels were unaffected by short-term treatment with antipsychotics in healthy volunteers. In the present study, we did not find significant differences in levels of adiponectin and leptin between patients and controls.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Adiponectin induces direct inhibition of proinflammatory pathways, including those regulated by toll-like receptors (TLRs) (Neumeier et al, 2006), via inhibition of NF-κB in several cell types (Lira et al, 2012). Hipoadiponectinemia has been found in schizophrenic patients (Hanssens et al, 2008) and antipsychotic therapy also contributes to this condition (Birkenaes et al, 2009;Oriot et al, 2008;Wampers et al, 2012), suggesting that antipsychotic medication may influence adiponectin homeostasis.…”
Section: Antipsychotics Glucose Intolerance Insulin Resistance and mentioning
confidence: 98%